Properties of the Rotation and Mergence of Twisted Gaussian Schell Model Array Beams Propagating in Turbulent Biological Tissues - Xianyang, Yang; Wenyu, Fu (International Journal of Optics, 2022)
In this paper, an analytical expression for describing propagation properties of twisted Gaussian Schell model array (TGSMA) beams through turbulent biological tissues is derived based on the extended Huygens Fresnel integral. With the help of the formulae, properties of the rotation and mergence for the TGSMA beams in turbulent biological tissues are researched in detail. It is found that the TGSMA beams go through the distinct mergence period in the far field besides phenomena of abruption and rotation in the near field, and turbulent biological tissues play a dominated role in mergence of the TGSMA beams. These novel results may be helpful in optical trapping.